Analysis of the Effect of Cost of Debt, Cost of Equity, and Profit on Investment Decisions : A Study on Hospitality Sector Companies Listed on the Indonesia Stock Exchange for the Period 2019-2023 - Reni Gustira; Agus Zahron Idris (International Journal of Economics, Management and Accounting, 2025)
This study analyzes the effect of Cost of Debt, Cost of Equity, and Profit on investment decisions in hospitality industry companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. By using purposive sampling method, this study involved 21 companies as samples, resulting in 105 observation data. Investment decision as the dependent variable is measured using Capital Expenditure (CapEx), while Cost of Debt, Cost of Equity, and profit as independent variables are calculated based on financial statement data. Multiple regression analysis is used to test the relationship between variables. The results showed that Cost of Debt, Cost of Equity, and Profit have a significant effect on investment decisions in the hospitality industry.